Indigenization text features in contemporary local architecture - Hamza, Abass Ali; Ibraheem, Suaad Khaleel; Mubarak, Arwa Mohammed (Iraqi Journal of Architecture and Planning, 2017)
Abstract The impact of the rapid progress of technology on local architecture features, led the so to chaos in architectural production and lack of harmony with each other, in particular, and with the general context in general, bore with two trends contradictory problematic firstly originality and return to the local architecture values and its assets and the second modernity and liberation of the old and the impossibility of return to the past.Confirmation continuity of civilization would have to come through innovation and Indigenization in the architectural expression and linked to the concepts of modernity, the identity of the concept of a significant effect in determining the way we understand architecture of the surroundings in which we live. Find it here tried to delve deeper into the study of features of the text of indigenization contemporary local architecture in terms of research problem came to the (Lack of clarity in the relationship between a features of the text of indigenization and technology in contemporary local architecture). And requests to achieve this theoretical framework to build features of the text of indigenization projects and apply this term to the draft General Secretariat of the Council of Ministers and then put the search results and to reach final conclusions about how to Features of indigenize projects and its role in the formation of contemporary domestic architecture.